Revisiting materials for teaching languages for specific purposes - Jesús García Laborda (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Teaching materials in languages for specific purposes have evolved in the last few years dramatically. The Internet currently plays a significant role in such development and has permitted both a wider range of resources and its free availability almost anywhere in the World. This paper presents a selection of different types of recent materials for English for Specific Purposes. The paper begins by defining ESP. Then it approaches how materials should shape the student’s own learning, how materials should be selected according to the different skills and then emphasizes the importance of the Internet as a source of materials. The paper concludes with a set of ideas for the future development of ESP materials. The final goal of this paper is to provide the readers with valuable tools that can enhance their teaching through accessible means